Regulating Digital Health Services in Indonesia: Legal Challenges, Liability Issues, and the Protection of Patient Rights - Herman Saputra; Herika Nofita; Muhammad Hatta (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2025)
The rapid development of information technology has facilitated the emergence of digital health services such as telemedicine, e-health, and mobile health, which enhance efficiency, accessibility, and the overall quality of healthcare delivery. However, this digital transformation also generates legal challenges that necessitate clear regulatory frameworks, particularly concerning the protection of patients’ personal data, the determination of medical liability in remote healthcare interactions, and the validity of electronic evidence in legal processes. This study aims to analyze the legal framework governing technology-based healthcare services in Indonesia and to identify the obstacles encountered in their implementation and enforcement. The research employs a normative juridical method with a statutory approach, drawing upon a literature review of relevant regulations, including the Health Law, the Electronic Information and Transactions Law, and implementing regulations issued by authorized institutions. The findings indicate that although Indonesia has established a legal framework for digital health services, the regulations remain sectoral and lack comprehensive standards, especially regarding medical liability, patient data protection, and oversight of digital platforms. Furthermore, implementation challenges persist due to weak inter-agency coordination, limited digital security infrastructure, and low legal and digital literacy among service providers and users. The study concludes that regulatory harmonization and the formulation of specific legislation are essential to ensure legal certainty, accountability, and the protection of patients’ rights within Indonesia’s digital healthcare ecosystem.